PENGARUH KUALITAS PRODUK DAN KEPERCAYAAN NASABAH MELALUI RELATIONSHIP MARKETING TERHADAP KINERJA PEMASARAN PT. BPR NUR ABADI KABUPATEN BULELENG - I Gusti Made Oka Astana; Kadek Doni Ariani (ARTHA SATYA DHARMA, 2021)
The purpose of this study was to determine the effect of product quality and customer trust through relationship marketing on the marketing performance of PT. BPR Nur Abadi, Buleleng Regency. The sample selected in this study were 100 people with . Methods of collecting data by distributing questionnaires and data analysis techniques using the smartPLS application. The results of this study state that the parameter coefficient value of Product Quality on Relationship Marketing is positive and significant where the coefficient value is 0.137 and the t value is 0.549 which is greater than the t table. Customer trust in Relationship Marketing is positive and significant where the coefficient value is 0.053 and the t value is 0.342 which is greater than the t table. Product Quality on Marketing Performance is positive and significant where the coefficient value is 0.088 and the t value is 0.398 which is greater than the t table. Customer Trust in Marketing Performance is positive and significant where the coefficient value is 0.309 and the t value is 0.570 which is greater than the t table. Relationship Marketing on Marketing Performance is positive and significant where the coefficient value is 0.153 and the t value is 0.227 which is greater than t table. The positive coefficient value and the t value is greater than t table, so it can be stated that the results of this study are significant, so the first to fifth hypotheses are accepted.